'This sickness is not hospital sickness': a qualitative study of the evil eye as a source of neonatal illness in Ghana. Issue 2 (17th March 2020) - Bell, April J.; Arku, Zelda; Bakari, Ashura; Oppong, Samuel A.; Youngblood, Jessica; Adanu, Richard M.; Moyer, Cheryl A.
Abstract: Previous research has described the evil eye as a source of illness for pregnant women and their newborns. This study sought to explore the perceptions of the evil eye among mothers whose newborns had experienced a life-threatening complication across three regions of Ghana. As part of a larger, quantitative study, trained research assistants identified pregnant and newly delivered women (and their newborns) who had survived a life-threatening complication at three tertiary care hospitals in southern Ghana to participate in open-ended, qualitative interviews about their experiences in March–August 2015. All interviews were audio-recorded and transcribed verbatim into English and analysis using the constant comparative method of theme generation. A total of 37 mothers were interviewed, 20 about neonatal illnesses and 17 about maternal illnesses. Six of the 20 mothers interviewed about their newborn's illnesses spoke at length about the evil eye being a potential cause of newborn illness. The evil eye was described in a variety of terms, but commonalities included a person looking at a pregnant woman, her newborn baby, the baby's clothes and even the mother's food, causing harm, even unintentionally. Prevention required mothers covering themselves while pregnant and keeping the baby away from others until it was old enough to ward off the evil eye. Treatment required traditional medicine, yet some indicated that allopathic medicine could help. The evil eye appears to serve a social control mechanism, encouraging pregnant women to dress modestly, stay indoors as much as possible and behave appropriately. The evil eye is a pervasive, universally understood phenomenon across three regions of Ghana, even amongst a hospitalized population receiving allopathic health care for life-threatening complications of childbirth. Understanding the role of the evil eye in newborn illness attribution is important for clinicians, researchers and programmatic staff to effectively address barriers to care seeking.